New Evidence of the Impact of the National Drug Price Negotiation Policy on the Availability, Utilization, and Cost of Anticancer Medicines in China: An Interrupted Time Series Study - Gao X; Yu M; Sun Y; Zhang T; Li X; Zhang L; Wang C (Dove Medical Press, 2024)
Xingyuan Gao,1,2 Man Yu,3 Yuyang Sun,3 Tiansi Zhang,1 Xin Li,1,3,4 Lingli Zhang,5 Changqing Wang1 1School of Health Policy and Management, Nanjing Medical University, Nanjing, People's Republic of China; 2Simcere Zaiming Pharmaceutical Co., Ltd., Nanjing, People's Republic of China; 3School of Pharmacy, Nanjing Medical University, Nanjing, People's Republic of China; 4Center for Global Health, School of Public Health, Nanjing Medical University, Nanjing, People's Republic of China; 5School of International Pharmaceutical Business, China Pharmaceutical University, Nanjing, People's Republic of ChinaCorrespondence: Changqing Wang, School of Health Policy and Management, Nanjing Medical University, Jiangning District, Nanjing, 211166, People's Republic of China, Email cqwang@njmu.edu.cn Lingli Zhang, School of International Pharmaceutical Business, China Pharmaceutical University, Jiangning District, Nanjing, 211198, People's Republic of China, Email zhanglingli@cpu.edu.cnPurpose: The increasing global burden of cancer has become a significant challenge for public health. The Chinese government introduced the National Drug Price Negotiation (NDPN) policy with the goal of lowering the prices of innovative drugs and enhancing their accessibility. This study aims to evaluate the impact of the 2021 NDPN policy on the availability, utilization, and cost of anticancer medicines in China.Methods: Data was gathered from 1519 hospitals between April 2021 and December 2022, with a focus on eight anticancer drugs affected by the 2021 NDPN policy. The availability, Defined Daily Doses (DDDs), and cost per Defined Daily Dose (DDDc) before and after the intervention were evaluated through interrupted time series analysis.Results: The NDPN policy resulted in a substantial 5.10% increase in the availability of anticancer drugs (p < 0.001). Utilization also experienced a significant surge, with an immediate increase of 11,254.36 DDDs (p < 0.001) and a monthly increase of 1208.28 DDDs (p < 0.001) following policy implementation. The DDDc decreased by US$ 111.00 (p < 0.001) immediately after the policy. Disparities in regional drug utilization were evident, with higher usage in the eastern region.Conclusion: The 2021 NDPN policy has notably enhanced the availability and utilization of anticancer medications in China while reducing their cost, in line with the policy's objectives. However, continuous monitoring is essential to ensure sustained access and to tackle regional disparities in drug utilization.Keywords: anticancer medicines, national drug price negotiation, China, availability, utilization, cost, interrupted time series analysis